Cost-Utility of Reduction Mammaplasty Assessed for the Brazilian Public Health System. (November 2014) - Araújo, Carlos Delano Mundim; Veiga, Daniela Francescato; Hochman, Bernardo Sérgio; Abla, Luiz Eduardo Felipe; Oliveira, Ana Carolina Salles; Novo, Neil Ferreira; Veiga-Filho, Joel; Ferreira, Lydia Masako
Background: Economic evaluation is important for making decisions about resource allocation. Few cost-utility or cost-effectiveness studies on breast hypertrophy have been reported in the medical literature. Objectives: The authors sought to determine the cost-utility of reduction mammaplasty in the Brazilian national health care system. Methods: This randomized controlled study was conducted in a university-affiliated hospital. Sixty patients with breast hypertrophy were enrolled prospectively and were assigned randomly to either the control group (n = 30 patients who received follow-up for 6 months) or the treatment group (n = 30 patients who underwent reduction mammaplasty). Direct costs were recorded, and the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) was administered to both groups at the beginning of the study (preoperatively for the treatment group) and 3 and 6 months postoperatively. Utility was determined with Instrument 6D of the Brazilian version of the Short-Form Health Survey (SF-6D), from the SF-36 data. Results: At the 6-month follow-up, the treatment group showed an improvement in utility, with an average direct cost of approximately £104. Conclusions: Reduction mammaplasty performed in the Brazilian national health care system provides a cost-utility ratio equivalent to approximately £142 per 1 quality-adjusted life year.